Influence of acidic pH on the formulation of TiO2 nanocrystalline powders with enhanced photoluminescence property - Moges Tsega; F.B. Dejene (Heliyon, 2017)
Titanium dioxide (TiO2) nanoparticles were prepared by the sol-gel method at different pH values (3.2–6.8) with a hydrochloric acid (HCl) solution. Raw samples were calcined at 500 °C for 2 h. The effects of pH on the structural, morphological and optical properties of TiO2 nanoparticles were investigated. At pH 4.4–6.8, only the anatase phase of TiO2 was observed. Under strong acidic condition at pH 3.2 rutile, brookite and anatase co-exist, but rutile is the predominant phase. The strain value increased and the crystallite size decreased as the HCl content increased. The increased crystallite sizes in the range 21–24 nm and enhanced blue emission intensity around 432 nm was obtained for the sample at pH 5.0. Experimental results showed that TiO2 nanoparticles synthesized at pH 5.0 exhibited the best luminescence property with pure anatase phase.